2017
DOI: 10.1016/j.bjm.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori with East Asian-type cag PAI genes is more virulent than strains with Western-type in some cag PAI genes

Abstract: The severity of Helicobacter pylori-related disease is correlated with the presence and integrity of a cag pathogenicity island (cagPAI). cagPAI genotype may have a modifying effect on the pathogenic potential of the infecting strain. After analyzing the sequences of cagPAI genes, some strains with the East Asian-type cagPAI genes were selected for further analysis to examine the association between the diversity of the cagPAI genes and the virulence of H. pylori. The results showed that gastric mucosal inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
(28 reference statements)
1
10
0
1
Order By: Relevance
“…East Asian-type cagA is more virulent than Western-type cagA due to its stronger binding affinity for SHP2 and morphological transforming activities [41]. In agreement with Yuan et al, mucosal inflammation was significantly higher in patients infected with East Asian-type cagA strains in in vitro and in vivo studies, and East Asian-type cagA strains appear to be a major contributor to clinical severity and gastric carcinogenesis as compared with Western-type cagA [12]. Our findings are supported by a previous study that showed that H. pylori cagA sequences from a Korean population were associated with East Asian-type cagA (ABD) [42], while most of the cagA sequences from Thai patients were identified as Western-type cagA (ABC).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…East Asian-type cagA is more virulent than Western-type cagA due to its stronger binding affinity for SHP2 and morphological transforming activities [41]. In agreement with Yuan et al, mucosal inflammation was significantly higher in patients infected with East Asian-type cagA strains in in vitro and in vivo studies, and East Asian-type cagA strains appear to be a major contributor to clinical severity and gastric carcinogenesis as compared with Western-type cagA [12]. Our findings are supported by a previous study that showed that H. pylori cagA sequences from a Korean population were associated with East Asian-type cagA (ABD) [42], while most of the cagA sequences from Thai patients were identified as Western-type cagA (ABC).…”
Section: Discussionsupporting
confidence: 85%
“…Several published studies demonstrated that more than 90% of H. pylori strains from East Asian populations carry the cagA gene [10,11], but approximately 20-40% of strains from other regions are cagA negative. Based on the conserved five-amino acid repeat motif (EPIYA motif) at the carboxyl terminal, CagA is classified into two major genotypes: Western type and East Asian type; however, the genotype of East Asian CagA is closely linked with development of gastric cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Over and above different methods of ascertaining IP- and Helicobacter -status, the risk of the two being associated appeared considerably higher in Taiwan [ 65 ] than in Denmark [ 63 ]. This may relate to greater virulence conferred by East Asian-type cag pathogenicity island genes (manifest as gastric mucosal inflammatory cell infiltration; secretion of the pro-inflammatory cytokine, interleukin-8; and translocation of CagA into host cells) [ 75 ]. Even in Europe, a particular profile of antibodies against pathogenicity markers is predictive of the current disease burden and deterioration of IP over time [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial virulence factor is one of the contributing factors to the development of severe H. pylori-related diseases. The diversity of cagPAI region in the H. pylori genome may have a modifying effect on the pathogenic potential of the infecting strain [24].…”
Section: Discussionmentioning
confidence: 99%